Clint Eastwood - The iconic filmmaker and his work unofficial and unauthorised - Nathan, Ian (White Lion Publishing, 2023)
Explore the works of one of Hollywood's most renowned filmakers - the iconic Clint Eastwood
Keywords: Eastwood, Clint -- 1930-